Job dissatisfaction as a predictor of poor health among middle-aged workers: a 14-wave mixed model analysis in Japan - Oshio, Takashi (Scandinavian Journal of Work, Environment & Health, 2021)
' ' OBJECTIVE ': 'This study aimed to examine the association between job dissatisfaction (JD) and health outcomes among middle-aged workers. ' ' METHODS ': 'This study used longitudinal data comprising 156 823 observations of 24 056 workers (13 177 men and 10 879 women) collected from a 14-wave nationwide population-based survey in Japan that began in 2005, involving individuals aged 50–59 years. Mixed models were estimated to examine the association between JD and the risk of psychological distress (PD), poor self-rated health (SRH), and health-related resignation (HRR). ' ' RESULTS ': 'Across all waves, 20.9–32.5% of participants were dissatisfied with their jobs for at least one year before each wave. Mixed model results showed that this JD experience was associated with higher risks of PD, poor SRH, and HRR, with odds ratios (OR) of 1.96 [95% confidence interval (CI) 1.75–2.20], 1.33 (95% CI 1.26 –1.40), and 1.57 (95% CI 1.40 –1.75), respectively. A longer JD duration was associated with a higher risk of poor health. No substantial differences between genders were found regarding the association between JD and health outcomes. A separate analysis showed reverse causation from poor health to JD; poor health was significant in predicting later JD even when it was controlled for. ' ' CONCLUSIONS ': 'The results confirm that JD was predictive of poor health among middle-aged workers. Therefore, policymakers and managers should monitor the JD of their employees and improve their work environments to enhance their occupational health.
Keywords: health; Japan; job dissatisfaction; job satisfaction; mixed model analysis; predictor; psychological distress; self-rated health